Management of the Palaeozoic Palaeontological Heritage Associated With Metamorphic Bedrocks: Courel Mountains UNESCO Global Geopark (Spain) - Daniel Ballesteros; Manuel García-Ávila; José Diez; Ramón Vila; Xosé Barros; Juan Carlos Gutiérrez-Marco; Pablo Caldevilla; Martín Alemparte (Geoconservation Research)
The Spanish Courel Mountains UNESCO Global Geopark has strong educational and touristic resources despite limited preservation of Paleozoic invertebrate fossil assemblages within metamorphic rocks. The paleontological sites are managed by means of their inventory and integration in a Geographical Information System, the construction of virtual 3D fossil models, the creation of a fossil collection exhibition, the transport of large boulders with fossils to places such as tourist offices, and hiking trails to see ichnofossils. To enable geoconservation, the Palaeozoic paleontological sites are neither promoted nor frequently visited. Fossils found in the Geopark by paleontologists and fortuitously by local people or hikers are deposited and safeguarded in the Geological Museum and are available for eventual exhibition and paleontological studies.